CONSTRUCTING THE 'URBAN PROFILE' OF AN ANCIENT GREEK CITY: EVIDENCE FROM THE OLYNTHOS PROJECT. (December 2020) - Nevett, Lisa C.; Tsigarida, E. Bettina; Archibald, Zosia H.; Stone, David L.; Ault, Bradley A.; Akamatis, Nikos; Cuijpers, Elena; Donati, Jamieson C.; García-Granero, Juan José; Hartenberger, Britt; Horsley, Timothy; Lancelotti, Carla; et al.
Abstract : This article argues that a holistic approach to documenting and understanding the physical evidence for individual cities would enhance our ability to address major questions about urbanisation, urbanism, cultural identities and economic processes. At the same time we suggest that providing more comprehensive data-sets concerning Greek cities would represent an important contribution to cross-cultural studies of urban development and urbanism, which have often overlooked relevant evidence from Classical Greece. As an example of the approach we are advocating, we offer detailed discussion of data from the Archaic and Classical city of Olynthos, in the Halkidiki. Six seasons of fieldwork here by the Olynthos Project, together with legacy data from earlier projects by the American School of Classical Studies at Athens and by the Greek Archaeological Service, combine to make this one of the best-documented urban centres surviving from the Greek world. We suggest that the material from the site offers the potential to build up a detailed 'urban profile', consisting of an overview of the early development of the community as well as an in-depth picture of the organisation of the Classical settlement. Some aspects of the urban infrastructure can also be quantified, allowing a new assessment of (for example) its demography. This article offers a sample of the kinds of data available and the sorts of questions that can be addressed in constructing such a profile, based on a brief summary of the interim results of fieldwork and data analysis carried out by the Olynthos Project, with a focus on research undertaken during the 2017, 2018 and 2019 seasons.